Post-Mining Land Restoration from an Environmental Fiqh Perspective (A Case Study of PT. Ang and Fang Brother's Mining Excavation in Morowali Regency) - Gunawan Musa (Green Publisher Indonesia, 2026)
This study examines post-mining land restoration from the perspective of environmental fiqh, focusing on a case study of PT. Ang and Fang Brother (PT. AFB) in Morowali Regency, Indonesia. Mining activities significantly contribute to economic growth but also generate severe environmental degradation, including soil damage, water pollution, and ecosystem disruption. Although regulatory frameworks exist, their implementation often remains ineffective due to technical, financial, and governance constraints. Therefore, this study aims to analyze how environmental fiqh principles can strengthen post-mining restoration practices and enhance ecological sustainability. This research employs a qualitative approach using field research methods. Data were collected through in-depth interviews with company representatives and affected local communities, as well as documentation analysis of relevant policies and reports. The data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings reveal a significant gap between restoration planning and field implementation. While PT. AFB has established reclamation programs, issues such as poorly maintained revegetation, abandoned mining pits, and limited community involvement persist. Environmental fiqh principles, including hifzh al-bi’ah, islah al-ardh, and ihya al-mawat, are found to align with national regulations and provide a strong ethical foundation for restoration. In conclusion, integrating environmental fiqh into post-mining policies can enhance moral responsibility, strengthen community participation, and support sustainable land restoration.